1999
DOI: 10.1007/pl00011806
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess Intensification for Production of Novel Marine Bacterial Antibiotics Through Bioreactor Operation and Design

Abstract: : There is a lack of research into bioreactor engineering and fermentation protocol design in the field of marine bacterial antibiotic production. Most production strategies are carried out at the shake-flask level and lack a mechanistic understanding of the antibiotic production process, offering poor prospects for successful scale-up. This review shows that data need to be collated on media and physical optima differences between the trophophase and idiophase, along with investigations into the control mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 113 publications
2
26
0
Order By: Relevance
“…Culturing an isolate under altered conditions has been shown to encourage the production of antibiotics. Modifications of growth media that have been found to elicit the expression of secondary metabolite pathways include metals and amino acid additions (notably tryptophan; Palazzotto et al, 2015), as well as varied phosphate concentrations, carbon sources, nitrogen sources, and pH, to name a few (Bode et al, 2002;Iwai & Ōmura, 1982;Marwick, Wright, & Burgess, 1999;Weinberg, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Culturing an isolate under altered conditions has been shown to encourage the production of antibiotics. Modifications of growth media that have been found to elicit the expression of secondary metabolite pathways include metals and amino acid additions (notably tryptophan; Palazzotto et al, 2015), as well as varied phosphate concentrations, carbon sources, nitrogen sources, and pH, to name a few (Bode et al, 2002;Iwai & Ōmura, 1982;Marwick, Wright, & Burgess, 1999;Weinberg, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…External factors can also affect the growth of microorganisms and the production of antibiotics (Marwick et al, 1999). It has been reported that environmental factors such as temperature, pH, and incubation duration influence antibiotic production (Iwai et al, 1973).…”
Section: Microbiologymentioning
confidence: 99%
“…carbon or nitrogen source) sometimes has to be limited to keep the cells in the stationary phase, while the substrate needed for the formation of the desired product has to be present in excess. The cells at tropophase (or growth phase) generally have their secondary metabolism, such as antibiotic production, "switched off" until they reach the idiophase (or production phase) (Marwick et al, 1999).…”
Section: Nutrient Levelmentioning
confidence: 99%